Export production under exchange rate uncertainty - Udo Broll; B. Michael Gilroy; Elmar Lukas (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2008)
Given that a multinational enterprise can react flexibly upon exchange rate movements, international trade flows may be interpreted as an option. An enterprise will opt to export if the profits obtained from exporting under given exchange rate developments are greater than if foreign subsidiary sales were opted. Naturally, given negative exchange rate scenario situations, an enterprise will choose not to export. By virtue of a favorable exchange rate situation it may be more advantageous to implement the flexibility given by the inherent option exercise privilege. Interestingly, even taking account of entrepreneurial risk aversion aspects of enterprises, it is demonstrated that situations characterized by enhanced exchange rate volatility may still lead to greater export trade volumes.
Keywords: F31; J20; 330; Export; Exchange Rate Volatility; Risk Aversion; Real Option; Wechselkursrisiko; Export; Risikoaversion; Realoption; Hedging; Theorie